2008
DOI: 10.1007/s12103-007-9028-5
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Balanced Approach: Defining Police Roles in Responding to Domestic Violence

Abstract: Responding to domestic violence poses unique challenges to law enforcement officers. Prior research has focused on issues such as officer safety and arrest policies but overlooked a critical component-the officers' perception of their role in responding to domestic violence incidents. This study explores how police officers define their roles through the use of focus group interviews with detectives assigned to a domestic violence unit. Findings include the identification of three role perspectives. Recommenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…Second, the police subculture or officer perceptions of their roles in responding to domestic violence incidents may exert an influence as well. The police assume multiple social roles including fighting crime, maintaining order, and social services (Balenovich, Grossi, & Hughes, 2008; Cole & Smith, 1999). The role of a law enforcer or crime fighter is arguably the most valued by the police officers while social service positions—which are often associated with feminine characteristics—such as intervening in domestic violence cases, are less valued within the police subculture (Balenovich et al, 2008; Garcia, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the police subculture or officer perceptions of their roles in responding to domestic violence incidents may exert an influence as well. The police assume multiple social roles including fighting crime, maintaining order, and social services (Balenovich, Grossi, & Hughes, 2008; Cole & Smith, 1999). The role of a law enforcer or crime fighter is arguably the most valued by the police officers while social service positions—which are often associated with feminine characteristics—such as intervening in domestic violence cases, are less valued within the police subculture (Balenovich et al, 2008; Garcia, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The police assume multiple social roles including fighting crime, maintaining order, and social services (Balenovich, Grossi, & Hughes, 2008; Cole & Smith, 1999). The role of a law enforcer or crime fighter is arguably the most valued by the police officers while social service positions—which are often associated with feminine characteristics—such as intervening in domestic violence cases, are less valued within the police subculture (Balenovich et al, 2008; Garcia, 2005). Balenovich et al (2008) conducted focus group interviews with a group of detectives assigned to a domestic violence unit and found that most police officers perceive their role to be as that of a strict law enforcer and only secondarily see theirs as a service-oriented social role in domestic violence cases.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With police often being the first formal CJS support victims encounter, police attitude and behavior are critical, particularly for management of violent situations and provision of prosecution and restraining orders (Balenovich, Grossi, & Hughes, 2008;O'Dell, 2007). Subsequently, changes in the CJS remained of utmost importance for empowering IPV survivors to report and access existing formal legal support.…”
Section: Legal Support Systems and Ipvmentioning
confidence: 99%
“…movement of the 1800's saw the establishment of the numerous Societies for the Prevention of Cruelty to Children, the home, the wife and the children were considered property of the husband, and he could discipline them as he saw fit(Karmen, 2001). Until the 1970's, acts of domestic and family violence were considered the family's private business, and nothing was done about it(Balenovich, Grossi & Hughes, 2008).However, with the passage of the Violence Against Women Act of 1994, the federal government focused attention on women who had been the victim of intimate relationship violence, and billions of dollars have been allocated to all states for the prevention of family violence (Cho & Wilke, 2005). Violence and abuse occurs to people, regardless of social status, education, or income level.…”
mentioning
confidence: 99%